An Analysis of Escapism in Tennessee Williams’ “The Glass Menagerie” - Pangaribuan, Rotua; Hutapea, Sri Natalia (The Explora, 2020)
This study deals with Tennessee Williams’ work, The Glass Menagerie based onpsychological analysis. The characters in the play are intentionally made to identify the attitudesand behaviors of each character in order to give up clear descripion of the characters. In the GlassMenagerie there are three characters who try to escape from reality but they have differentpsychological problem in life. Living in illusion is Amanda’s way to escape, playing the glassfigure is the way of Laura to escape from reality, while the way of Tom to escape is going to themovies. The purpose of analyzing the literary work is to display clearly about the psychologicalelement in the play and also moral lesson clearly.